Risk Factors for Chronic Mastitis in Morocco and Egypt - Hanna N. Oltean; Amr S. Soliman; Omar S. Omar; Tamer F. Youssef; Mehdi Karkouri; Azza Abdel-Aziz; Ahmad Hablas; Taylor Blachley; Ali Tahri; Sofia D. Merajver (Hindawi Limited, 2013)
Chronic mastitis is a prolonged inflammatory breast disease, and little is known about its etiology. We identified 85 cases and 112 controls from 5 hospitals in Morocco and Egypt. Cases were women with chronic mastitis (including periductal, lobular, granulomatous, lymphocytic, and duct ectasia with mastitis). Controls had benign breast disease, including fibroadenoma, benign phyllodes, and adenosis. Both groups were identified from histopathologically diagnosed patients from 2008 to 2011, frequency-matched on age. Patient interviews elicited demographic, reproductive, breastfeeding, and clinical histories. Cases had higher parity than controls (OR = 1.75, 1.62-1.90) and more reported history of contraception use (OR = 2.73, 2.07-3.61). Cases were less likely to report wearing a bra (OR = 0.56, 0.47-0.67) and less often used both breasts for breastfeeding (OR = 4.40, 3.39-5.72). Chronic mastitis cases were significantly less likely to be employed outside home (OR = 0.71, 0.60-0.84) and more likely to report mice in their households (OR = 1.63, 1.36-1.97). This is the largest case-control study reported to date on risk factors for chronic mastitis. Our study highlights distinct reproductive risk factors for the disease. Future studies should further explore these factors and the possible immunological and susceptibility predisposing conditions.